2011
DOI: 10.1534/genetics.111.129700
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Parental Genome Blocks in Recombinant Inbred Lines

Abstract: We consider recombinant inbred lines obtained by crossing two given homozygous parents and then applying multiple generations of self-crossings or full-sib matings. The chromosomal content of any such line forms a mosaic of blocks, each alternatively inherited identically by descent from one of the parents. Quantifying the statistical properties of such mosaic genomes has remained an open challenge for many years. Here, we solve this problem by taking a continuous chromosome picture and assuming crossovers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…1. Although the assumptions in their study are different from ours-in particular we consider descent from multiple migrant individuals and the possibility of recombination between tracts from these individuals-the conclusion reached by Chapman and Thompson (2002) is essentially similar to the one reached here: tracts are not exponentially distributed when T is large relative to N. Martin and Hospital (2011) examined this problem further in the context of recombinant inbred lines and similarly concluded that tract lengths are not exponential.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…1. Although the assumptions in their study are different from ours-in particular we consider descent from multiple migrant individuals and the possibility of recombination between tracts from these individuals-the conclusion reached by Chapman and Thompson (2002) is essentially similar to the one reached here: tracts are not exponentially distributed when T is large relative to N. Martin and Hospital (2011) examined this problem further in the context of recombinant inbred lines and similarly concluded that tract lengths are not exponential.…”
Section: Resultssupporting
confidence: 61%
“…A single tract spanning a larger region may survive the first generations and then be broken up into smaller fragments in different individuals in the same region of the genome. Martin and Hospital (2011) also examined the problem of correlated tract lengths, but in the context of recombinant inbred lines, and similarly concluded that tract lengths are not independent.…”
Section: Liang and R Nielsenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even under the model of the sequential Markov coalescence (McVean and Cardin 2005;Marjoram and Wall 2006), the IBD tract length is not exponentially distributed, because the transition rate depends on the total branch length of the local tree, that is, the coalescent time in the case of two chromosomes. The nonexponential distribution for the length of IBD tracts has been modeled by Martin and Hospital (2011) in two-way RILs by sibling mating and by Chapman and Thompson (2003) in random mating populations, and their results show that the deviations from nonexponential distributions are acceptable, particularly for large populations.…”
Section: Discussionmentioning
confidence: 99%
“…A decisive contribution to such efforts is a theoretical analysis of different incompatibility models and their selection signatures in the genomes of RILs. Most of the theoretical work devoted to understanding the genomes of RILs has ignored the role of selection (e.g., Haldane and Waddington 1931;Broman 2005;Martin 2006;Teuscher and Broman 2007;Johannes and Colomé-Tatché 2011;Martin and Hospital 2011;Broman 2012;Zheng et al 2015). The exception is the early work by Haldane (1956), Reeve (1955), and Hayman and Mather (1953), who examined cases of selection against homozygotes at a single locus and described the changes in genotype frequencies as a function of inbreeding and selection.…”
mentioning
confidence: 99%